2003
DOI: 10.1046/j.1365-2672.2003.02011.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermented soya beans on diarrhoea and feed efficiency in weaned piglets

Abstract: Aims: To evaluate anti-diarrhoeal and growth enhancing properties of fermented soya beans in weaned piglets. Methods and Results: In a first phase piglet diet, toasted full-fat soya beans (20%) were replaced with either cooked soya beans or Rhizopus microsporus or Bacillus subtilis fermented soya beans. The effect on the incidence, severity and duration of diarrhoea in enterotoxigenic Escherichia coli (ETEC)-challenged weaned piglets was determined (pen trial, 24 piglets per treatment). Severity of diarrhoea w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
103
1
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(126 citation statements)
references
References 31 publications
(73 reference statements)
7
103
1
7
Order By: Relevance
“…There was a rapid initial increase in ETEC shedding in the faeces of challenged pigs immediately post infection followed by a gradual decrease. Others have reported the same pattern over a similar time period (Nabuurs et al, 1993;Kiers et al, 2003).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…There was a rapid initial increase in ETEC shedding in the faeces of challenged pigs immediately post infection followed by a gradual decrease. Others have reported the same pattern over a similar time period (Nabuurs et al, 1993;Kiers et al, 2003).…”
Section: Discussionsupporting
confidence: 57%
“…The oral challenge of pigs with pathogenic E. coli has been widely used as a model of PWC (Sarmiento et al, 1988;Nollet et al, 1999;Madec et al, 2000;Van Dijk et al, 2002;Kiers et al, 2003;Montagne et al, 2004). The experimental model used here produced prolonged faecal ETEC excretion in all challenged pigs post infection.…”
Section: Discussionmentioning
confidence: 99%
“…To remove the antinutritional factors and improve biological values of soyabean meal (SBM), many species of microbes such as lactic acid bacteria (Cho et al, 2007) and Bacillus subtilis (Kiers et al, 2003) have been used for fermenting SBM. This result indicated that SBM fermented with the optimal microbial proportions could reduce antigen protein by enzymatic hydrolysis and microbial fermentation as well as increase protein, lactic acid, probiotics, acid-soluble protein, total and most amino acid contents in fermented soyabean meal (FSBM), which is in agreement with previous reports (Hachmeister and Fung, 1993;Zhao et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports about FSBM application in piglets (Kiers et al, 2003;Feng et al, 2007;Lee et al, 2007;Song et al, 2010); however, few reports can be found for its application in sow's reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation